1987
DOI: 10.1007/bf01456346
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous thermocoagulation for sphenopalatine ganglion neuralgia

Abstract: The authors describe percutaneous radiofrequency (rf) thermocoagulation of the sphenopalatine ganglion used to treat seven patients with sphenopalatine ganglion neuralgia. The procedure was effective in relieving pain, without significant side-effects. All the patients have actually been free of pain during a follow-up of 6-28 months. The surgical technique and the rationale for its use are pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 13 publications
0
47
0
Order By: Relevance
“…Cell culture studies have shown that exposure creates a biological effect due to the induction of early gene expression in the dorsal horn. 13 RFTC has been used to destroy the tissue in TN, ablate tumor metastasis, perform lateral cordotomy in unilateral malignant pain, destroy dorsal root ganglion in spinal pain and treat discogenic back pain. But RF has a signal output which is typically a continuous wave of RF voltage, whereas PRF has a RF wave that is broken into short bursts of signal output.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture studies have shown that exposure creates a biological effect due to the induction of early gene expression in the dorsal horn. 13 RFTC has been used to destroy the tissue in TN, ablate tumor metastasis, perform lateral cordotomy in unilateral malignant pain, destroy dorsal root ganglion in spinal pain and treat discogenic back pain. But RF has a signal output which is typically a continuous wave of RF voltage, whereas PRF has a RF wave that is broken into short bursts of signal output.…”
Section: Discussionmentioning
confidence: 99%
“…Salar et al [14] reported the use of percutaneous RFTC of the SPG for sphenopalatine neuralgia in seven patients. Each received two lesions at 60°C and 65°C, respectively, for 60 seconds.…”
Section: Efficacy Of Sphenopalatine Ganglion Blockadementioning
confidence: 99%
“…It lies in the pterygopalatine fossa, which is approximately 1 cm wide and 2 cm high, and resembles a "vase" when visualized on a lateral fluoroscopic view. The pterygopalatine fossa is bordered anteriorly by the posterior wall of the maxillary sinus, posteriorly by the medial plate of the pterygoid process, medially by the perpendicular plate of the palatine bone, superiorly by the sphenoid sinus, and laterally it communicates with the infratemporal fossa [14]. The foramen rotundum, through which the maxillary branch of the trigeminal nerve passes, is located on the superolateral aspect of the pterygopalatine fossa, whereas the opening to the pterygoid canal, which houses the vidian nerve, is located on the inferomedial portion of the fossa.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…More recently, based on new hypotheses related to the pathophysiology of CH, the SPG has been added to the potential therapeutic targets [17,35,36]. The SPG has rich parasympathetic and sympathetic components.…”
Section: Rationale Of Radiosurgery Target For Sphenopalatine Ganglionmentioning
confidence: 98%